SURVEY TENTANG MINAT SISWA TERHADAP KEGIATAN EKSTRAKURIKULER OLAHRAGA DI SMA NEGERI 4 MALANG - Ilyasa, Muh. Ridho; Sudjana, I Nengah; Purnami, Sri (Jurnal Sport Science, 2016)
Abstract :The reseach results generally had been found that percentage score of students interest to the sports extracurricular activities in SMA Negeri (Public Senior High School) 4 Malang was 77.61%. Specifically seen from three sub-variables, attention obtained score 78.62%, willingness 77.99%, and pleasureÂ 76.23%. Thus, extracurricular in SMA Negeri 4 Malang obtained good response from studentsÂ who follow the activity.Conclusion in this research was in general student interest to the sports extracurricular activity in SMA Negeri 4 Malang included into good category. Specifically seen from attention aspect wich included into good category, willingness included into good category, and pleasure included into good category. Suggestion from this research was expected that the school conduct more improvement to the student interest in school, especially in the sports extracurricular activity.Key words :interest, extracurricular activity of sport.